Growth response of cocoa seedlings (Theobroma cacao L.) ICCRI 06 clone with application of manure and Trichoderma sp. - Cahyaningrum, Descha Giatri; Siwi, Kalista Hayu Margi; Sugiyarto, Sugiyarto; Harlianingtyas, Irma; Dinata, Gallyndra Fatkhu (Universitas Trunojoyo Madura, 2024)
The growth of cocoa seedlings (Theobroma cacao L.) is influenced by the use of the type of planting medium and the presence of supporting microorganisms, such as the Trichoderma sp. This research aims to determine the effect of giving Trichoderma sp. and manure on the growth of cocoa seedlings. The research used a factorial randomized block design (RBD) method consisting of 9 treatments which were repeated 3 times, so there were 27 experimental units. Factor 1 is chicken manure by 200, 300 and 400 g/polybag, factor 2 is Trichoderma sp. with different level of mixing. The parameters observed were plant height, number of leaves, stem diameter, wet weight of the crown, wet weight of the roots, dry weight of the crown, dry weight of the roots. The research results showed that M3 (400 g/polybag) gave the best results for the parameters of stem diameter, crown wet weight, root wet weight and root dry weight of cocoa plants. Giving Trichoderma sp. at a level of 10 mL L-1 gave the best results for stem diameter, root wet weight and root dry weight. The research results provide a positive contribution to the application of a combination of chicken manure (M1:200 g/polybag) with Trichoderma sp. (P2: 10 mL L-1) on stem diameter and root wet weight.